A Study to Assess the Quality of Life among the Gynecological Cancer Patients in Selected Hospitals of the City with a View to Develop an Information Booklet - Vijay Pawar, Pooja; Shinde, Marylin (International Journal of Nursing Research, 2023)
Aim: Quality of life (QOL) among women with gynecological cancer: Findings from a study conducted at select hospitals in the city for the purpose of producing an educational pamphlet. Introduction: Cancer is the main health issue in the community across the world. Globally, cancer is one of the most common causes for morbidity and mortality. Gynecological cancers include cervical cancer, endometrial cancer, gestational trophoblastic tumor, ovarian epithelial cancer, ovarian germ cell tumor, uterine sarcoma, vaginal cancer, and vulvar cancer. Materials and Methods: In this study, cross-sectional, descriptive, and research design was used to evaluate the QOL among the gynecological cancer patients. Ninety-four gynecological cancer patients from the hospital of the city are selected for the study as a sample. Non-probability purposive sampling technique was used. A Likert-style scale with four options used for analysis. Results: Majority of the patients 61 (64.89%) were not have any changes in global health status QOL, 19 (20.21%) were somewhat worse level in their global health status/QOL, 12 (12.76%) were somewhat better level on scale, 2 (2.12%) were in much worse level, and none of the patients were in much better level on global health status/QOL. Majority of the patients 50 (53.19%) were have moderate symptoms, 37 (39.36%) were have minor symptoms, 6 (6.38%) were have serious symptoms, and 1 (1.06%) not have substantial symptoms on symptoms scale items. Conclusion: According to the results of this study, the QOL of gynecological cancer patients does not change. On the physical, emotional, social, and role-function dimensions of QOL, gynecological cancer and its treatment processes have a detrimental impact.